2019
DOI: 10.1111/socf.12504
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Variation in State Concealed Carry Laws, 1970–2016

Abstract: Why do some U.S. states have more permissive concealed carry weapons (CCW) laws than other states? To answer this question, this study tests several plausible social, political, and economic factors thought to affect the likelihood of this outcome over several decades. Models estimated using random‐effects ordered logistic regression reveal that theoretical accounts based on partisan politics, gendered politics, economic threat, and racial threat largely explain variation in CCW laws over time. Tests for inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…That is, when individuals, especially for those occupying privileged social positions, perceive that their racial, political, class, or gender status are under threat, they turn to guns to alleviate/supplement these fears. For example, negative attitudes toward racial minorities among individuals have been found to increase fear of crime which, in turn, increases gun ownership and support for gun rights (Felson and Pare 2010;Kaplan 2016, 2017;Malone and Steidley 2019;O'Brien et al 2013;Young 1985). When men perceive a loss of power, such as increased female employment or (perceived) potential unemployment, they are also more likely to turn to guns to reassert their power and take on a masculine protector status (Carlson 2015;Cassino and Besen-Cassino 2020;.…”
Section: Firearms: Who and Why?mentioning
confidence: 99%
See 2 more Smart Citations
“…That is, when individuals, especially for those occupying privileged social positions, perceive that their racial, political, class, or gender status are under threat, they turn to guns to alleviate/supplement these fears. For example, negative attitudes toward racial minorities among individuals have been found to increase fear of crime which, in turn, increases gun ownership and support for gun rights (Felson and Pare 2010;Kaplan 2016, 2017;Malone and Steidley 2019;O'Brien et al 2013;Young 1985). When men perceive a loss of power, such as increased female employment or (perceived) potential unemployment, they are also more likely to turn to guns to reassert their power and take on a masculine protector status (Carlson 2015;Cassino and Besen-Cassino 2020;.…”
Section: Firearms: Who and Why?mentioning
confidence: 99%
“…Alternatively, when political elites and movements do not align, movements/organizations are less effective at getting movement-congruent policies passed; however, there is evidence that other forms of political activism, such as recruitment and campaigns, increase in part due to the threat posed by counter-movement successes (Austin 2002;Gusfield 1963;Maxwell and Parent 2012;Tarrow 2021). When considering the gun rights movement, extant research has found that Republican legislative make-up increases the adoption of gun rights legislation; conversely, Democratic legislative make-up decreases gun rights adoption (Malone and Steidley 2019;Steidley 2018). Moreover, recent work has found that, over time, gun ownership has become increasingly important in whether an individual reports they are Republican-further highlighting the convergence of gun rights and Republican identities (Joslyn et al 2017).…”
Section: (Political) Threat and Firearmsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we expect that schools located in states that tend to support and elect Republican politicians will be more likely to have shooting sports organizations. Literature pertaining to the sociology of guns has consistently shown that the Republican Party has been integral to the advancement of gun rights in the United States (e.g., Malone and Steidley 2019; Mullins and Kavish 2017; Steidley 2018; Stucky et al 2008; Thompson and Stidham 2010). The NRA also endorses and donates money to Republican politicians at much higher rates than Democratic politicians (Weiss and Gould 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Another growing line of research within sociology identifies the characteristics of U.S. gun culture (Mencken and Froese 2019; Yamane 2017; Yamane, Yamane, and Ivory 2020). Finally, still other sociologists have explored factors associated with political expansions of gun rights in the United States (Malone and Steidley 2019; Steidley 2018).…”
Section: Introductionmentioning
confidence: 99%